THE INFLUENCE OF GREEN TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT FODDMART SAMARINDA - Ramadhani, Ayu; Wediawati, Tuti; Khairil Anwar; Ummi Nadroh (BEMJ : Business, Entrepreneurship, and Management Journal, 2025)
This study aims to analyze the influence of green transformational leadership and organizational culture on the performance of Foodmart Samarinda employees. In the context of increasingly fierce retail business competition, companies are required not only to improve efficiency and productivity but also environmental awareness. Foodmart Samarinda faces challenges in maintaining and improving employee performance amidst operational demands and sustainability requirements. The research employed a quantitative method with a causal associative approach, using the entire population of Foodmart Samarinda employees, totaling 34 people, as a saturated sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that green transformational leadership has a positive and significant influence on employee performance, evidenced by a positive beta coefficient and a significance value of 0.006 (< 0.05). Meanwhile, organizational culture also shows a significant influence on employee performance, but with a negative beta coefficient and a significance of 0.006 (< 0.05), indicating aspects of the culture that need improvement. These two variables simultaneously explain 33.9% of the variation in employee performance, with the remainder explained by other variables outside the model. Therefore, it is recommended for Foodmart Samarinda management to strengthen green transformational leadership and evaluate and adjust relevant organizational culture elements to support optimal employee performance improvement.